Desarrollo de un recorrido virtual interactivo del Campus Salache y extensiones La Maná y Pujilí de la Universidad Técnica de Cotopaxi usando la metodología kanban - Aguilar Inga, Omar Samael (2022)
This proposal is oriented to the development an interactive virtual tour accessible through the internet to disseminate the physical, technological and recreational infrastructure of the Technical University of Cotopaxi regarding its campus Salache, extensions La Maná and Pujilí. For this purpose, a bibliographic collection process has been carried out in order to define the most appropriate hardware and software tools for the implementation of virtual tours, as well as field research to collect different points of view from those involved. Once the requirements have been identified, the Kanban methodology was applied with the intention of coordinating the make of each one of the tasks required for running the virtual tour. It should be noted that in order to obtain a realistic result, 360° images have been captured with FishEyes format and converted through web technologies to equirectangular format. In the same way, audio and descriptive texts have been included through .net technology, C# programming language, a persistence layer based on directories and files with which is obtained a functional system for the benefit of the Technical University of Cotopaxi. The validation of the proposal is done through regression tests applied to the campus authorities and beneficiary extensions of the tour who through their expertise in each of their respective areas indicate satisfactory points of view towards the development made.